Evaluation of Vegetable Oil Extraction Methods on Crude Oil Yields in Indonesia. Systematic Literature Review - Saputra, Hendra; Azrifirwan, Azrifirwan; Firdani, Fea (GreenTech, 2024)
The method of extracting vegetable oils greatly affects the optimal yield and can affect the composition of the fatty acids that make up the triglycerides contained in the resulting oil. Systematic literature review method with research topics regarding the evaluation of the development of oil extraction methods for crude oil produced from 300 selected articles, then selected to become the following 100 articles into 25 relevant articles, obtained research data carried out to obtain optimum results is method Soxhlet extraction. From 25 articles, 4 articles were selected, which carried out optimization and follow-up on the oil results obtained, namely by purifying the oil and applying it to the product. This extraction method has not been developed on an industrial scale, only on a research or laboratory scale. The most widely used in the process of extracting oil on an industrial scale is the screw method, or known as the screw press.